Reactivation of memory-associated neurons induces downstream suppression of competing neuronal populations - Jacob F. Norman; Bahar Rahsepar; Anna Vena; Martin Thunemann; Anna Devor; Steve Ramirez; John A. White (Proceedings of the National Academy of Sciences, 2025)
Inducing apparent memory recall by tagging and optogenetically reactivating cells in the hippocampus was demonstrated over a decade ago. However, the hippocampal dynamics resulting from this reactivation remain largely unknown. While calcium imaging is commonly used as a measure of neuronal activity, GCaMP, the most common calcium indicator, cannot be used with optogenetic neuronal reactivation because both require blue light excitation. To resolve this overlap, we demonstrate optogenetic reactivation with a red-shifted opsin, ChrimsonR. We then conduct dual-color calcium imaging in CA1 during memory reactivation in DG. In addition to measuring population dynamics in CA1, CA1 cells tagged during the original experience were identified. In the fear-conditioned animals (FC+), nontagged cells in CA1 decreased their firing rate during stimulation, while tagged cells maintained their activity level. In the FC+ animals, as the behavioral effect of stimulation decreased across days, so did the changes in neural activity during stimulation. Our results both demonstrate the technical feasibility of calcium imaging during optogenetic reactivation of memory-associated neurons and advance our understanding of the dynamics underlying this reactivation.